Prospective green constitution in new and renewable energy regulation - Qurbani, Indah Dwi; Rafiqi, Ilham Dwi (Legality : Jurnal Ilmiah Hukum, 2022)
The format for regulating new and renewable energy in the draft law on new and renewable energy in Indonesia still contains many polemics and problems. This is motivated by various problems of conception and substance in it, such as misconceptions about nomenclature, problems with institutional formats, licensing problems, and the accommodation of nuclear energy. This paper aims to analyze the potential impacts and prospects of energy using a green constitution point of view. This study used normative juridical research with a statutory and conceptual approach. The results show that the environment is the dominant entity affected by energy management and utilization activities, both fossil energy and new renewable energy with different potential impacts. The prospect of a green constitution has been contained in the draft law on new and renewable energy, but it cannot be realized optimally because transition policies in Indonesia still have dual orientations and overlapping arrangements. The principles of a green constitution can be a guiding concept and norm for the format of regulation and implementation of the use and utilization of new and renewable energy so that it is in line with the values ​​of environmental protection and preservation.